2008
DOI: 10.1506/ap.7.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Evidence on the Constructive Capitalization of Operating Leases*

Abstract: One type of relevant ex ante research supporting the accounting standard-setting process is the study of a proposed standard's impact on reported figures. The International Accounting Standards Board recently decided to review the lease accounting standard, which will naturally involve consideration of the G4 ϩ 1 recommendation to capitalize all noncancellable lease contracts, including operating leases. National evidence of the impact of the G4 ϩ 1 proposals provides feedback for the international standard-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 19 publications
4
39
1
9
Order By: Relevance
“…In addition; it has been determined that the unrecorded lease liabilities are as much as 89.5% of the reported liabilities on average and the unrecorded assets are as much as 39.4% of the reported assets. Durocher (2008) has examined the impact of the reflection of the operating leases belonging to 100 companies having the highest revenue in 2002 and 2003 and whose securities have been traded in Canadian stock market on the balance sheet on the financial indicators under certain assumptions (interest rate, total life cycle of the lease/consumed life cycle/remaining life cycle and tax rate). The results have shown that the reflection of the operating leases on the balance sheet has caused to significant increases in the liabilities and assets and for this reason, there shall be a significant increase in the ratio of liability/asset and a significant decrease in the current ratio and the impacts of the operating leases on the income statement are less important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition; it has been determined that the unrecorded lease liabilities are as much as 89.5% of the reported liabilities on average and the unrecorded assets are as much as 39.4% of the reported assets. Durocher (2008) has examined the impact of the reflection of the operating leases belonging to 100 companies having the highest revenue in 2002 and 2003 and whose securities have been traded in Canadian stock market on the balance sheet on the financial indicators under certain assumptions (interest rate, total life cycle of the lease/consumed life cycle/remaining life cycle and tax rate). The results have shown that the reflection of the operating leases on the balance sheet has caused to significant increases in the liabilities and assets and for this reason, there shall be a significant increase in the ratio of liability/asset and a significant decrease in the current ratio and the impacts of the operating leases on the income statement are less important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this study indicated that capitalizing operating leases could increase the debt-to-asset ratio and decrease the current ratio significantly. These results were noted across all industry segments in the sample, whereas significant impacts on return on assets, return on equity and/or earnings per share were noted in only three industry segments: merchandising and lodging, oil and gas, and financial services (Durocher, 2008). Another study in 2008 in Germany (Fulbier, Pferdehirt, & Silva, 2008) analysed the impact of operating lease capitalization for a sample of 90 companies belonging to the three major indices (DAX 30, MDAX and SDAX) for the years 2003 and 2004.…”
Section: "The Objective Of the Lease Project Is To Develop A Standamentioning
confidence: 80%
“…Many scholars have studied leases (Barone et al, 2014); while some of them have focused on the effect on stock market prices (Ro, 1978, Bowman, 1980, most of them have focused on the analysis of the impact of capitalization of operating leasing on key financial ratios (Ashton, 1985, Imhoff, Lipe, & Wright 1991, Beattie V. et al, 1998, Goodacre, 2003, Durocher, 2008, Jesswein, 2009, Grossman & Grossman 2010, Singh, 2010, Fitò, Morgan & Orgaz, 2013, Nuriani, Hengb, & Jeliesta, 2015.…”
Section: "The Objective Of the Lease Project Is To Develop A Standamentioning
confidence: 99%
“…The remaining rental expense is considered as depreciation of leased assets. To provide results comparable to prior researches - Imhoff , Lipe Wright (1991, 1993, 1997, Opperman (2013), Durocher (2008), Beatie (2006), Bennett, Bradbury (2003), Mulford, Gram (2007), the research is focused on non-fi nancial companies reporting under IFRS indexed on BCPP. There were 25 companies with securities listed on BCPP in December 2013.…”
Section: Aim and Methodologymentioning
confidence: 88%